COVID-19 status and utilisation of essential maternal and child healthcare services during the pandemic in Ahmedabad, India - Sandul Yasobant; K Shruti Lekha; Ravina Tadvi; Bhavin Solanki; Walter Bruchhausen; Deepak Saxena (BMC Pregnancy and Childbirth)
Abstract Background Access to essential healthcare services is pertinent to the achievement of universal health coverage in any nation. The COVID-19 lockdown was used to mitigate the spread of the pandemic. Consequently, there was a reduction in the Utilisation of Basic Healthcare Services (UBHS) in diverse dimensions. However, variation existed in the UBHS by COVID-19 status, but the extent of this disparity has not been extensively addressed in Ahmedabad, India. Therefore, this study explores the relationship between COVID-19 status and utilisation of essential maternal and child healthcare services during the pandemic in Ahmedabad, India. Methods A mixed-method approach was used for the data (both quantitative and qualitative) collection from November 2021 to October 2022. Four zones were purposefully selected from the 6 zones in Ahmedabad. The quantitative part of the study included pregnant women or those who had a baby delivery from April 2020 to October 2021 (n = 278), while 10 of these women participated in the qualitative part. Data were analysed using descriptive statistics, Chi-square test, and binomial logistic regression (α = 0.05). A deductive approach was used to analyse the qualitative data. Results Of the total 278, almost 43% of the women were infected with COVID-19 during their pregnancy. Women who tested positive availed lesser antenatal care (ANC), and Postnatal care (PNC). There were diverse experiences documented regarding access to essential maternal and child healthcare services during the pandemic. Women without COVID-19 are more likely to receive maternal healthcare services, such as visits of any healthcare workers [aOR = 2.59 (1.03- 6.49)], counseling services [aOR = 1.92 (0.61- 6.06)], delivery at the planned place [aOR = 1.98 (0.99- 3.92)] as compared to those who are positive. Women without COVID-19 were more likely to be accompanied by healthcare workers during labor ([aOR = 2.91(1.04- 8.11) and to receive appropriate birth spacing counselling [aOR = 1.38 (0.7–2.71)]. Conclusion Utilisation of essential maternal and child healthcare services was lower among women who were COVID-19 positive compared to those who were not. Social and health system determinants for disrupting healthcare services during the pandemic were fear of infection and unavailability of the health workforce. Health planners and policymakers are encouraged to take into consideration of these findings while building resilient health care for managing future pandemics.